FUNERAL AND COMMEMORATIVE RITES AMONG THE KABARDIANS IN THE 1920S: BETWEEN TRADITION AND ISLAMIC PSEUDO-ORTHODOXY - Lakunova, Diana Ruslanovna (History, Archeology and Ethnography of the Caucasus, 2025)
Funeral and commemorative rites are valuable ethnographic sources that reflect a mix of traditional and modern religious practices. This article examines the funeral and commemorative ceremonies of the Kabardians in the Kabardino-Balkarian Republic and the impact of “new” Islamic movements on these rituals. The majority of Kabardians adhere to Sunni Islam, yet their rituals often retain elements of ancient beliefs, which has created friction with “new” Muslims. These new movements advocate for a return to orthodox Islam, leading to contradictions and the gradual replacement of old ritual practices with new ones. To document these changes, the author conducted fieldwork from 2022 to 2024 in several villages and cities across the region, including Baksanenok, Kishpek, and Zayukovo of the Baksan region; Argudan and Anzorey of Lesken region; Altud of Prohladnenskoe region; Zalukokoazhe of Zolskyi region; Baksan, Nalchik, and Nartkala cities. The study also employed participant observation to analyze individuals and groups in their natural social environment. Analysis of the collected data reveals that many traditional Kabardian rites and behavioral norms have either lost their original meaning or fallen into disuse. Others have been transformed and modified, while some entirely new practices have emerged under the influence of modern Islamic trends. The study concludes that ethnographic research in this area is crucial for understanding the diversity and dynamics of local culture amidst globalization and religious transformation.